The Development of a Short-Distance Running Learning Model Based on Colorful Balls Run Games for Phase C Students - Prabowo, Andika; Raibowo, Septian; Bogy Restu Ilahi; Syafrial; yarmani; Meliana; Sugihartono, Tono; Dian Pujianto (UNIB Press, 2025)
This study aims to develop a short-distance running learning model based on colorful balls run games for phase C students at elementary school 106 Bengkulu City. This research is a type of Research and Development (R&D) employing the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The method used is descriptive qualitative. The research population consisted of phase C students at elementary school 106 Bengkulu City, with the sampling technique using total sampling. The research instruments included observation, interviews, questionnaires, and documentation. Based on the validation results, material experts obtained a score of 92% and media experts obtained 88%, both categorized as